Identification of Insects on Soybean Planting at UPT Pengembangan Benih Padi dan Palawija Singosari - Yenny Wuryandari; Annisa Zukhruf Oktavia Salamah (Future Science, 2023)
Corruption obliteration presently focuses on three main issues: prevention, obliteration, and asset recovery. Eradicate corruption not only focuses on preventing and eradicating but also improves the terms of punishing the perpetrators and is also associated with seeking to recover state financial losses from the proceeds of corruption crimes. The provisions in question are of great hope for systematic and comprehensive anti-corruption measures, which feature not only criminal prosecution of corruption crimes but also the protection of national finance, that is, the obligation to return state funds from the perpetrators of criminals. Corruption crimes can be used for national development. Therefore, normatively it would not be excessive if the provisions of Article 18 of Constitution no. 31 of 1999 in conjunction with Constitution no. 20 of 2001 regarding the Obliteration of deceits of corruption can be an effective legal instrument for compensating the State for losses caused by corruption crimes.